Feasibility and Safety of Active Physiotherapy in the Intensive Care Unit for Intubated Patients with Malignancy - N. Gautheret; C. Bommier; A. Mabrouki; V. Souppart; A. S. Bretaud; E. Ghrenassia; J. Le Roy; J. Lambert; E. Azoulay; V. Lemiale (Medical Journals Sweden, 2023)
Objectives: Physiotherapy leads to improvements in critically ill patients who receive mechanical ventilation. However, cancer patients have not been included in previous studies on this subject. This study explored the feasibility and safety of physiotherapy in the intensive care unit for patients with malignancy. Design: Observational prospective single-centre study, comparing cancer and control patients. Patients: All consecutive patients admitted to the intensive care unit who needed invasive mechanical ventilation for more than 2 days with no contraindication to physiotherapy were included in the study. Methods: The main outcome was the proportion of physiotherapy sessions at the prescribed level in each group. Results: A total of 60 patients were included within 1 year. A total of 576 days were screened for physiotherapy sessions and 367 physiotherapy-days were analysed (137 days for control patients and 230 days for cancer patients). The ratio of physiotherapy sessions performed/prescribed did not differ between groups: 0.78 (0.47-1) in the control group vs 0.69 (0.6-1) in the cancer group (odds ratio 1.18 (IC95% 0.74-1.89); p = 0.23). A sensitivity analysis including patient effect as random variable confirmed those results (odds ratio 1.16 (0.56-2.38), p = 0.69). Adverse events occurred with the same frequency in cancer patients and non-cancer patients. Conclusion: Physiotherapy in cancer patients who require intubation is feasible and safe. However, only two-thirds of prescribed physiotherapy sessions were performed. Studies are warranted to explore the barriers to physiotherapy in the intensive care unit setting. LAY ABSTRACT Mobilization for intubated patients improves outcomes. However, patients with malignancy have not been included in previous studies exploring mobilization in the intensive care unit (ICU). This study explored the feasibility and safety of mobilization for intubated patients with malignancy. Intubated patients with and without cancer were included in an observational study. Each day, a mobilizing team, including a physiotherapist, decide on the mobilization level for individual patients, according to their awakening and motor status. The physiotherapist performed the physiotherapy sessions. The level obtained during physiotherapy sessions was compared with the prescribed level. A physiotherapy session was considered successful when the prescribed level was obtained. Statistical analysis of 27 non-cancer patients and 33 cancer patients did not reveal any differences in terms of the feasibility and safety of physiotherapy sessions. However, in this study, only two-thirds of prescribed physiotherapy sessions were performed. Barriers to the use of physiotherapy in the ICU for patients with malignancy should be explored.